Diagnostic Efficacy of Enhanced Visual Assessment [Visual Check] for Triaging Cervical Cancer Screen Positive Women - Saritha Shamsunder; Archana Mishra; Anita Kumar; Rajni Beriwal; Charanjeet Ahluwalia; Sujata Das (Journal of Mid-Life Health, 2024)
Introduction: Colposcopy is important for triaging any abnormal cervical screening test. Scarcity of trained colposcopists and colposcopy centers is a big hurdle to screening programs in low- and middle-income countries. Objectives of the Study: The objective was to assess the performance of the artificial intelligence incorporated into the mobile optical device technologies (ODT) Enhanced Visual Assessment (EVA visual check) against physician colposcopic diagnosis and the gold standard of histopathology. Materials and Methods: It was a cross-sectional observational study conducted on women referred to a colposcopy clinic following an abnormal screening test. Colposcopic examination was performed by colposcopists using the MobileODT EVA system. Physician’s impression and Visual Check analysis were compared with the final histopathological analysis or cytology. Cases with normal cytology and normal colposcopy did not undergo biopsy, and these were considered normal. Results: A total of 2050 women were screened, and 147 screen-positive women were recruited in the study. EVA Visual Check had a sensitivity of 86.8% (75–95), specificity of 28.7% (20–39), positive predictive value (PPV) of 40.7% (32–50), negative predictive value (NPV) of 79.4% (62–91), and diagnostic accuracy of 49.7% (41–58) for diagnosing cervical intraepithelial neoplasia (CIN) 1+ lesions. EVA Visual Check has a sensitivity of 89.3% (72–98), specificity of 26.1% (18–35), PPV of 22.1% (15–31), NPV of 91.2% (76–98), and diagnostic accuracy of 38.1% (30–46) for CIN 2+ lesions. Conclusion: MobileODT EVA colposcope with AI has sensitivity comparable to physician’s diagnosis, whereas specificity, PPV, and NPV were less than that of physician’s diagnosis. It could prove valuable for triage of screen-positive women for further management.